The Relevance of Variants With Unknown Significance for Autism Spectrum Disorder Considering the Genotype–Phenotype Interrelationship - Lovato, Diogo V.; Herai, Roberto R.; Pignatari, Graciela C.; Beltrão-Braga, Patricia C.B. (Frontiers in Psychiatry, 2019)
Several efforts in basic and clinical research have been contributing to unveiling the genetics behind Autism Spectrum Disorders (ASD). However, despite these advancements, many individuals diagnosed with ASD and related neuropsychiatric conditions have been genetically investigated without elucidative results. The enormous genetic complexity of ASD-related conditions makes it a significant challenge to achieve, counting with a growing number close to a thousand of genes involved belonging to different molecular pathways and presenting distinct genetic variations. Next Generation Sequencing (NGS) is the approach most used in genetic research related to ASD, identifying “de novo” mutation, which is closely related to more severe clinical phenotypes, especially when they affect constrained and loss-of-function intolerant genes. On the other hand, “de novo” mutations findings contribute for a small percentage of ASD population since most of the cases and genetic variants associated with neuropsychiatric conditions are inherited, and phenotypes are results of additive polygenic models, which makes statistical efforts more difficult. As a result, sometimes NGS investigation can sound vainly or unsuccessful, and new mutations on genes already related with ASD are classified as Variants of Unknown Significance (VUS), hampering their endorsement to a clinical phenotype. This review is focused on currently available strategies to clarify the impact of VUS and to describe the efforts to identify more pieces of evidence throughout clinical interpretation and genetic curation process.